Oral rehabilitation after removal of a central cemento-ossifying fibroma - Clóvis Lamartine de Moraes Melo Neto; Liogi Iwaki Filho; Karina Rosso; Rodrigo Lorenzi Poluha; Bruna Milhomens de Sousa; Sérgio Sábio (Editorial Ciencias Médicas, 2019)
Introduction: The cemento-ossifying fibroma is a benign bone neoplasm that affects mainly the female sex during the third or fourth decades of life. This lesion has a slow growth and the treatment is the surgical removal of the tumor, because radiotherapy is not indicated. Objective: to describe and discuss a case of central cemento-ossifying fibroma. Case report: A 41-year-old female patient sought dental treatment due to tooth mobility in the anterior region of the mandible. In this region of the mandible, an increase in volume was noted with a firm consistency on palpation, covered by normal mucosa, and displacement of teeth. Radiographically, the presence of an extensive lesion in this region was observed. An incisional biopsy was performed which led to the final diagnosis of central cemento-ossifying fibroma. Subsequently the tumor was completely removed. An autogenous bone graft was performed and four osseointegrated implants were installed to rehabilitate the patient. Implant-supported prostheses (lower arch) and a complete denture (upper arch) were installed to restore esthetics and function of the patient's oral cavity. Conclusions: Despite being a benign tumor, the central cemento-ossifying fibroma caused functional and aesthetic damage to the patient and required a complex rehabilitation treatment. After approximately 5 years of tumor removal, there was no recurrence of the lesion or signs of peri-implant or periodontal diseases, evidencing the success of the treatments.